Championing Open Research: Lessons from the Lab - THIBAULT, Guillaume (Institutional Knowledge at Singapore Management University, 2024)
Lightning talk “Championing Open Research: Lessons from the Lab” by Winner of the Singapore Open Research Awards 2024, Associate Professor Guillaume THIBAULT from Nanyang Technological University. Abstract: As a strong advocate for open research, my motivation stems from the belief that transparency and accessibility are fundamental to advancing biological sciences. By making all data, methods, and code related to my research publicly available, I ensure that my work is reproducible, reusable, and accessible to the global research community. While these practices may take additional time, they are essential for ensuring the integrity and long-term value of my findings. My laboratory adheres to the FAIR principles — Findable, Accessible, Interoperable, and Reusable — through open repositories like DR-NTU (Data) and platforms like Protocols.io for method documentation. This approach enhances collaboration and accelerates discovery, contributing to impactful advancements in health and disease research. Website: https://libguides.ntu.edu.sg/SGopenresearchawards/Thibault